2013
DOI: 10.1097/mib.0b013e3182810122
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated Fatty Acids in Inflammatory Bowel Diseases

Abstract: Recent epidemiological studies highlight the key role of the type of consumed unsaturated fatty acid and the development of ulcerative colitis (UC). We aimed to review the potential mechanisms behind the antiinflammatory effects of unsaturated fatty acids on intestinal inflammation, to discuss their potential limitations, and to propose a new reappraisal of polyunsaturated fatty acids (PUFAs) in the pathophysiology of inflammatory bowel disease (IBD). A literature search using PubMed was carried out to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(46 citation statements)
references
References 130 publications
0
46
0
Order By: Relevance
“…A potential mechanism to explain the inverse association between fish and CD is through marine ω3 PUFA content in fish 15, 4750 . Dietary ω3 PUFA may inhibit, through competitive mechanisms, formation of pro-inflammatory leukotrienes and prostaglandins through the arachidonic pathway and also inhibit adaptive immune responses through the peroxisome proliferator-activated receptor pathway 50 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A potential mechanism to explain the inverse association between fish and CD is through marine ω3 PUFA content in fish 15, 4750 . Dietary ω3 PUFA may inhibit, through competitive mechanisms, formation of pro-inflammatory leukotrienes and prostaglandins through the arachidonic pathway and also inhibit adaptive immune responses through the peroxisome proliferator-activated receptor pathway 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Dietary ω3 PUFA may inhibit, through competitive mechanisms, formation of pro-inflammatory leukotrienes and prostaglandins through the arachidonic pathway and also inhibit adaptive immune responses through the peroxisome proliferator-activated receptor pathway 50 . Additionally, ω3 PUFA may inhibit vascular adhesion, migration and angiogenesis 50 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arachidonic acid (AA), an n-6 PUFA is a precursor to generation of pro-inflammatory eicosanoids such as leukotriene B4 (LTB4), this conversion occurring through a series of enzymatic steps 16, 18 . On the other hand, n-3 polyunsaturated fatty acids like docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) have anti-inflammatory effects through generation of resolvins, protectins, and other endogenous factors that down regulate inflammation 16, 18 . Genome-wide association studies (GWAS) have identified that genetic variation can influence plasma and tissue n-3 and n-6 PUFA concentrations and their biological pathways 19-21 .…”
Section: Introductionmentioning
confidence: 99%
“…Omega-3 polyunsaturated fatty acids such as docosahexanoic acid (DHA) and eicosapentaenoic acid (EPA) are potent anti-inflammatory and immunoregulatory agents in a wide variety of diseases associated with chronic inflammation, including metabolic syndrome [22], neurodegeneration [23], inflammatory bowel diseases [24], cardiovascular disease [25], and cancer [26]. DHA- and EPA-induced anti-inflammatory responses are mediated by their respective bioactive mediators such as resolvins and protectins, which act as inhibitors of leukocyte infiltration and signaling activity of inflammatory cytokines, particularly TNF-α [27,28].…”
Section: Introductionmentioning
confidence: 99%